Dental resin composites: A review on materials to product realizations. (1st February 2022) - Cho, Kiho; Rajan, Ginu; Farrar, Paul; Prentice, Leon; Prusty, B. Gangadhara
Abstract: Dental resin composites have revolutionized dental care and enabled minimally invasive dentistry to preserve healthy tooth structure and provide natural-appearing esthetic results; these materials are now good alternatives to metal and amalgam restorations. Nevertheless, dental composites are being further developed to enhance their long-term clinical performance and longevity. With a complete understanding of the various material characteristics and design strategies of dental composite systems, frontiers of dental restoration research can aim towards creating novel materials that can produce very similar properties, functionalities, and internal structures as hard dental tissues. In this review article, the authors present an overview of the synthesis of the advanced dental composite systems with the recent research and development fields over the last 5 years. This review also explores how to control and optimize the required properties of the composites, ideally to increase the longevity/durability of restorations preventing recurrent caries. Research studies and commercial products are introduced to forecast the demands and trends of resin-based dental composites, in order to assist clinicians and researchers in optimal selection of materials to fulfill mechanical, physical, biological, and functional requirements. Graphical abstract: Image 1